Enteric viral infections among domesticated south american camelids: First detection of mammalian orthoreovirus in camelids - Castilla D. (2021)
This study was supported by CONCYTEC-FONDECYT en el marco de la convocatoria ?Proyecto Investigaci?n B?sica 2019-01? (grant numbers 355-2019) and by the Vicerrectorado de Investigaci?n y Posgrado de la Universidad Nacional Mayor de San Marcos en el marco de la convocatoria ?Proyecto de Investigaci?n con financiamiento para Grupos de Investigaci?n 2021?. This study was also partially supported by the Conselho Nacional de Desenvolvimento Cient?fico e Tecnol?gico (CNPq grant numbers 404984/2018-5 and 301469/2018-0) and the Funda??o Carlos Chagas de Amparo ? Pesquisa do Estado do Rio de Janeiro, Brazil (FAPERJ, grant number E-26/202.909/2017).